The Influence of Emotional Intelligence and Effective Communication on Interpersonal Relationship Quality and Life Satisfaction in Indonesia - Rachmi, Rachmi; Asri, Aswati; Sa'diyah, Sa'diyah; Nuswantoro, Patriandi; Mokodenseho, Sabil (Eastasouth Institute, 2024)
This study examines the complex relationships between interpersonal relationship quality (IRQ) and life satisfaction (LS) among people in Indonesia, with a focus on the roles played by emotional intelligence (EI) and effective communication (EC). Structural Equation Modeling with Partial Least Squares (SEM-PLS) was used as a quantitative method to examine the associations between the variables in a sample of 210 people. The findings show strong and favorable correlations: EC and EI have a positive impact on LS and IRQ. A number of fit indices indicate the structural model's satisfactory fit, and the blindfolding test confirms the model's predictive ability. The results indicate that, in the Indonesian setting, developing emotional intelligence and effective communication skills may lead to improved interpersonal connections and a higher quality of life.